(3JGQjN ecIs - (3eMeO Hf YHO GdcQje GdGRQbj, CHh GdhdjO,J (B223 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdCLd YeQ Hf YHO GdeLjO GdejGfTi bGd cYH cGfJ GdcYHI ZKG eMdi GdeGA bHd Cf jNdb Gddg YR hLd GdSehGJ hGdCQV HCQHYjf SfI s
(3BNQgG (B:s
(3hGdQGMI Ohf GdMOjHjI Ydi jSGQ GdPGgH Edi MHI GdHZjHZI hGdHZjHZI HChGNQ Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(140) s
Keywords: (3GdJGQjNs